The Impact of Histopathological Features on the Prognosis of Oral Squamous Cell Carcinoma: A Comprehensive Review and Meta-Analysis - Dolens, Eder da Silva; Dourado, Mauricio Rocha; Almangush, Alhadi; Salo, Tuula A.; Gurgel Rocha, Clarissa Araujo; da Silva, Sabrina Daniela; Brennan, Peter A.; Coletta, Ricardo D. (Frontiers in Oncology, 2021)
Objective: Over many decades, studies on histopathological features have presented high-level evidence of contribution for treatment directions and prognosis of oral squamous cell carcinoma (OSCC), but also provided inconsistencies, making clinical application difficult. The 8th TNM staging system of OSCC has acknowledged the importance of some histopathological features, by incorporating depth of invasion (DOI) to T category and extranodal extension (ENE) to N category. The aim of this systematic review with meta-analysis is to determine the most clinically-relevant histopathological features for risk assessment and treatment planning of OSCC, and to elucidate gaps in the literature. Methods: A systematic review was conducted using PRISMA guidelines, and the eligibility criteria were based on PECOS (population, exposure, comparison, outcome and study type). PubMed, Cochrane, Scopus and Web of Science were searched for articles exploring the impact of histopathological features on OSCC outcomes with Cox multivariate analysis. Pooled data were subjected to an inverse variance method with random effects or fixed effect model, and the risk of bias was evaluated using QUIPS (quality in prognosis studies). Quality of evidence was assessed with the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) criteria. Results: The study included 172 articles published from 1999 to 2021. Meta-analyses confirmed the prognostic potential of DOI, ENE, perineural invasion, lymphovascular invasion and involvement of the surgical margins, and brought promising results for the association of bone invasion, tumor thickness and pattern of invasion with increased risk for poor survival. Although with a small number of studies, the results also revealed a clinical significance of tumor budding and tumor-stroma ratio on predicted survival of patients with OSCC. Most of the studies were considered with low or moderate risk of bias, and the certainty in evidence varied from very low to high. Conclusion: Our results confirm the potential prognostic usefulness of many histopathological features and highlight the promising results of others; however, further studies are advised to apply consistent designs, filling in the literature gaps to the pertinence of histopathological markers for OSCC prognosis.